Repetitive symbolic play as a therapeutic process - Campbell, Megan (Rhodes University, Faculty of Humanities, Department of Psychology, 2009)
Child centred play therapy theory explains that the facilitative environment of the relationship between child and play therapist allows the child the opportunity to confront emotional pain imbedded in lived, relational experiences, and in so doing process and gain mastery over it. However very little research exists into how the child, through his use of repetitive, symbolic play, as a therapeutic process, achieves this resolution. This research project aims to address this gap in research by exploring and describing repetitive symbolic play as a therapeutic process within child centred play therapy that facilitates change in the child"Ÿs sense of self, assisting him towards healthy adjustment. The research project uses a young boys"Ÿ therapeutic process as a case study, employing a qualitative research design that draws from interpretative research. Fourteen repetitive play sequence themes were analysed within the context of the case formulation and follow-up feedback meetings that took place throughout the therapy process. Using a hermeneutic enquiry the researcher illustrates how the child"Ÿs sense of self, dependent on his perceptions of his external environment, became far more congruent, as evident through his behaviour, when his environment, first in play therapy, then at home and at school became more consistent, supportive and nurturing. Within this facilitative environment the researcher then describes how the child used repetitive symbolic play to address and process emotional issues relating to earlier experiences within his external environment. Hermeneutic analysis suggests that the child"Ÿs use of repetitive symbolic play within the facilitative relationship between him and his therapist became a therapeutic process in and of itself that contributed towards self-directed healing, and change within his sense of self, that promoted healthier adjustment within his environment.
Keywords: Play therapy; Symbolic play; Child psychology; Developmental psychology